(untitled) (Journal of Economics and Sustainability, 2021)
The households’ savings in Malaysia have shown a deteriorating trend that negatively impacts their financial security. The Financial Inclusion and Capability Study of BNM (2016) indicates that merely 6 percent of Malaysians could survive for more than six months and 18 percent up to three months if they lose their main source of income. Thus, it is imperative to examine the drivers of future savings of Malaysian households. A sample of 1,106 bank customers in three cities of peninsular Malaysia was recruited, and the descriptive statistics, correlation analysis, and Seemingly Unrelated Regressions (SUR) were employed. The results reveal that about 25 percent of households are not likely to make any changes in their savings profile in various financial and physical assets. The drivers of future saving are found to be socio-demographic parameters, such as age, education level, the number of working members in the household, and income, and other parameters, such as the percentage of income saved, and the period of the saving plan, which have a significant relationship with the change in future savings of the households. The policy implications of the findings are also presented. Received 20 July 20. Revised 9 August 20. Accepted 11 August 20.